Escuchando el sonido: concepciones sobre acústica en alumnos de distintos niveles educativos - Perales Palacios, F. Javier (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1997)
In recent years, many articles have been published on students' preconceptions of different theoretical concepts in Physics. Howewer, one area of this discipline which has received very little attention is that of Acoustics. This article first examines Acoustics from a wide range of perspectives, placing it within a scientific, didactic, and sociological framework. Secondly, it analyzes the results of a test given to students of different ages and levels in order to identify common preconceptions of Acoustics. Finally a reflection about the possible implications these might have for the Physics classroom is made.